The Influence of Product Quality, Packaging, and Promotion on Purchasing Decisions Tempeh Chocolate Awicho Ngawi - Trisnowati, Juni; Anisa Yumarti, Nurul (Jurnal Ekuisci, 2023)
This research aims to determine the influence of product quality, packaging, and promotion on the purchase decision of Awicho Ngawi tempeh chocolate both partially and simultaneously. The population in this study is consumers of Awicho Ngawi tempeh chocolate, where the number cannot be known with certainty. Sampling in this study used accidental sampling technique. The research data was obtained by distributing questionnaires and interviews about product quality, packaging, and promotion, as well as purchasing decisions to 70 respondents. The analytical techniques used include a multiple linear regression analysis, F test, t-test and coefficient of determination (R2), as well as using SPSS applications. The results showed that product quality, packaging, and promotion had a significant effect on the purchase decision of Awicho Ngawi tempeh chocolate, both partially and simultaneously. Nilai adjusted R square (R 2) of 0.654, meaning that independent variables consisting of product quality, packaging, and promotion affect the purchase decision of Awicho Ngawi tempeh chocolate by 0.638 or 65.4%, while the remaining 0.362 or 36.2% is influenced by other variables that were not studied in this study.